The Effect of Using Extensive Reading Approach on Improving Students’ Reading Rates at Tenth Grade of SMA Genta Syaputra Teluk Naga Tangerang in Academic Year 2018/2019 - Muhammad Ricky Yuliansyah (Foremost Journal, 2020)
ABSTRACT Reading rate indicates the amount of time taken by the student to read a story. Reading rate reduced readers' text comprehension when compared with comprehension levels while reading at an unrestricted rate. Therefore reading should be mastered by students because it helps them to improve their reading speed. This research aimed to help on improving students' reading rates. The researcher used purposive sampling technique. The total population of SMA Genta Syaputa 232 students of tenth grade in academic 2018/2019. This research used Extensive Reading approach to improves students' reading rates. By involving the activities of extensive reading, students are not only expected to resolve their problem but also increase their reading rate. The result showed that had a significantly positive effect on the English reading rates.